Bryoflora of urban territories of Kharkiv oblast (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The paper presents the results of research of Kharkiv bryoflora and the three largest cities of Kharkiv region: Izum, Balakleya and Kupiansk. The list of bryophyte flora is given. It contins information about 104 species and varieties briofitiv and their occurrence in different types of natural and man-made habitats in the studied cities, as well as missing and erroneously of given form. 11 species are newly discovered in Kharkiv region: Bryum dichotomum, B. funckii, B. kunzei, B. subapiculatum, B. violaceum, Grimmia laevigata, Schistidium apocarpum, Didymodon vinealis, Orthotrichum diaphanum, O. striatum and Campylophyllum calcareum. A classic structural analysis of bryoflora urban areas was hold. We gave a rough estimate of the potential bryophyte flora species diversity in undisturbed natural coenoses in modern Kharkiv.
Keywords: bryoflora, Kharkiv, Balakliia, Izium, Kupiansk.